HOSPITAL MANAGEMENT RELATED TO PATIENT LOYALTY VIEWING FROM SERVICE QUALITY, SATISFACTION, IMAGE AND VALUE - Suyanto S (Universal Institute of Professional Management, 2026)
Health development in Indonesia aims, among others, at making quality, equitable, and proportionate health services accessible to the Indonesian population. Various development efforts have been implemented to realize this objective, including improvements in infrastructure, the quality of medical personnel, accessibility, healthcare service processes, and the professional attitudes demonstrated by hospitals. This study aims to analyze patient loyalty from the perspectives of service quality, hospital image, perceived value, and patient satisfaction among inpatients in Type B hospitals in Bandung City. A total of 296 inpatients from Type B hospitals in Bandung City were selected using accidental random sampling as the research sample. This study employed the Structural Equation Modeling (SEM) method, with data analyzed using AMOS software. The results indicate that, out of the ten proposed hypotheses,